Socio economy status (SES) and parental background influence the achievement among students in SMK Seksyen 24 (1), Shah Alam, Selangor / Ku Mohd Hafiezad Ku Shaif @ Ku Shuib - Ku Shaif @ Ku Shuib, Ku Mohd Hafiezad (2014)
This study is focused on aspects of socio economy status (SES) and parental background, their environment influence the academic achievement among students. The studies is carried out in order to examine the significant relationship between students’ academic achievement, relationship, environment and their parental background in SMK Seksyen 24 (1), Shah Alam, Selangor. There are 80 respondents who were actively involved in questionnaires were administered randomly in order to obtain information and responses regarding their socio economy status (SES) and parental background. Questionnaires were the instruments used in gathering data on students and their parents. Responses from the students and their parents were treated statistically using frequency tables (pie chart), percentages, mean, standard deviation and Chi Square as the tools. The findings from this study indicated that there is a significant relationship existing between the socio economy status (SES) and parental background on the student’s academic achievement among students in SMK Seksyen 24(1) Shah Alam, Selangor. Based on the findings, suggestions in the form of recommendations are offered, which included the extremely role of the parents, students, teachers, school, society and Ministry of Education in Malaysia toward student justification performance.